ANALISIS STRUKTUR GERAK TARI GIOMU DI SANGGAR MOGUSATO KABUPATEN BOLAANG MONGONDOW UTARA - Riski Mokodompit; Riana Diah Sitharesmi; Nurlia Djafar; Rahmawati Ohi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Traditional dance plays a crucial role as a medium for cultural expression, representing the values, identity, and social structure of its supporting communities. However, academic studies often lack a clear gap between theoretical understanding and actual performance practices. In the context of the Giomu Dance, a court dance of the Kaidipang community in North Bolaang Mongondow Regency, previous research has tended to be descriptive-historical and has not yet explored its movement structure in depth as practiced by cultural performers. This study aims to systematically analyze the movement structure of the Giomu Dance by examining movement vocabulary, spatial design, and performance dynamics. The study employed a descriptive qualitative approach, with data collection techniques including performance observations, in-depth interviews with cultural figures and dancers at the Mogusato Studio, and visual documentation. The results indicate that the movement structure of the Giomu Dance is composed of five main vocabulary elements interconnected through planned transitions and repetitions, four floor patterns that establish dramatic relationships between female and male dancers, and movement dynamics that emphasize gentleness, order, and resilience. These findings reveal that the movement structure of the Giomu Dance represents the values of unity, honor, and nobility of Kaidipang women, rooted in the local historical and socio-cultural context. This study concludes that the Giomu Dance functions not only as a welcoming performance art but also as a medium for articulating cultural identity that remains relevant and sustainable in the lives of the people of North Bolaang Mongondow today.